ASSESSMENT OF THE TOXIC POTENTIAL OF A MIXTURE OF ASPARTAM AND SORBIC ACID WITH BIOASSAY - M. V. Zaytseva; N. M. Suraeva; A. V. Samoilov (Пищевые системы, 2022)
The biomarkers of the subchronic toxicity of binary mixtures of food additives sorbic acid and aspartame in concentrations of 50, 100 mg/l and 500, 1000 mg/l, respectively, were studied using plant biotests. A comparative analysis of the indicators such as biomass gain, a level of production of the oxidative stress marker, malondialdehyde (MDA), and dynamics of accumulation of proliferative and cytogenetic disorders was carried out after incubation of Allium cepa roots in the aqueous solutions of these compounds. A significant delay in the root growth (more than 60%) was observed in the combinations of sorbic acid and aspartame of 50/1000 and 100/500 mg/l compared to the control. However, significant differences in the effects on root mass gain were not revealed after analysis of the results of treatment with additives individually and with their mixture. It was found that upon treatment with the mixture of additives, only sorbic acid influenced root mass gain, while the interaction of these compounds was insignificant. An effect of the combined impact of sorbic acid and aspartame on the proliferative activity of meristem cells was more negative than upon treatment in the mono-mode in the similar concentrations. This indicator was affected by both sorbic acid and aspartame; however, the preserving agent again played the leading role. Moreover, the level of proliferation also depended on the effect of the interaction between these additives. The antagonistic effect in regard to the indicator of the oxidative stress was not recorded when treating with the mixture of these additives; although, the MDA level in roots increased more than twice upon individual treatment with sorbic acid, while aspartame, on the contrary, reduced its level by half. The obtained results can be used to monitor and predict early consequences of effects of combinations of sorbic acid and aspartame in the food composition.